2013
DOI: 10.3892/or.2013.2610
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ERα inhibits proliferation and invasion of MKN28 gastric cancer cells by suppressing β-catenin

Abstract: Abstract.The relationship between estrogen receptor (ER)α and patient prognosis has been identified in gastric cancer; however, the definite role of ERα in gastric cancer remains to be fully elucidated. The aim of the present in vitro study was to investigate the impact of ERα on cell proliferation, migration and invasion in gastric cancer cell lines. We investigated the biological effect of ERα overexpression on gastric carcinoma cells. An MKN28 gastric cancer cell line stably overexpressing ERα was establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…In the current study, patients who were >60 years old had significantly lower levels of ESR2 mRNA in tumoral compared with healthy gastric tissue samples; however, all ESR2 splicing variants were analyzed simultaneously. A previous study suggested that ESR1 may exhibit antiproliferative activity, and reduce the motility and invasion of GC cells (64). Furthermore, ESR1 has been associated with an early TNM stage in GC (18).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, patients who were >60 years old had significantly lower levels of ESR2 mRNA in tumoral compared with healthy gastric tissue samples; however, all ESR2 splicing variants were analyzed simultaneously. A previous study suggested that ESR1 may exhibit antiproliferative activity, and reduce the motility and invasion of GC cells (64). Furthermore, ESR1 has been associated with an early TNM stage in GC (18).…”
Section: Discussionmentioning
confidence: 99%
“…However, other researchers have demonstrated the expression of both receptors in GC (62)(63)(64). Zhou et al (65) found that the expression of β-catenin was reduced when ERα was overexpressed, and this resulted in a decrease in growth and proliferation of GC cells, and an increase in the apoptotic rate by preventing entry into the G 1 /G 0 phase. ER-α is considered a rare subtype of estrogen receptor ERα, which is associated with increased Figure 2.…”
Section: Gastric Cancer (Gc)mentioning
confidence: 99%
“…Previous studies found that men are at higher risk of developing gastric cancers. Zhou et al (2013) reported that estrogen hormones are protective against gastric cancer. Overexpression of estrogen receptor can decrease motility and invasion of cancer cells by inhibiting cell growth and malignant progression.…”
Section: Prevalence Of Gastric Premalignant Lesionmentioning
confidence: 99%